FEVER OF UNKNOWN ORIGIN (FUO) AND INFLAMMATION OF UNKNOWN ORIGIN (IUO): IS 18F-FDG-PET/CT A USEFUL FIRST LINE DIAGNOSTIC STRATEGY? - Schoenau, V.; Vogel, Kristin; Engelbrecht, M.; Schmidt, D.; Kuwert, Torsten; Manger, Bernhard; Schett, Georg (2016)
EVALuna2:13472

The value of (18)F-FDG-PET/CT in identifying the cause of fever of unknown origin (FUO) and inflammation of unknown origin (IUO): data from a prospective study - Schoenau, Verena; Vogel, Kristin; Englbrecht, Matthias; Wacker, Jochen; Schmidt, Daniela; Manger, Bernhard; Kuwert, Torsten; Schett, Georg (Annals of the Rheumatic Diseases, 2017)
Fever of unknown origin (FUO) and inflammation of unknown origin (IUO) are diagnostically challenging conditions. Diagnosis of underlying disease may be improved by (18)F-fluorodesoxyglucose positron emission tomography ((18)F-FDG-PET).Prospective study to test diagnostic utility of (18)F-FDG-PET/CT in a large cohort of patients with FUO or IUO and to define parameters that increase the likelihood of diagnostic (18)F-FDG-PET/CT. Patients with FUO or IUO received (18)F-FDG-PET/CT scanning in addition to standard diagnostic work-up. (18)F-FDG-PET/CT results were classified as helpful or non-helpful in establishing final diagnosis. Binary logistic regression was used to identify clinical parameters associated with a diagnostic (18)F-FDG-PET/CT.240 patients were enrolled, 72 with FUO, 142 with IUO and 26 had FUO or IUO previously (exFUO/IUO). Diagnosis was established in 190 patients (79.2%). The leading diagnoses were adult-onset Still's disease (15.3%) in the FUO group, large vessel vasculitis (21.1%) and polymyalgia rheumatica (18.3%) in the IUO group and IgG4-related disease (15.4%) in the exFUO/IUO group. In 136 patients (56.7% of all patients and 71.6% of patients with a diagnosis), (18)F-FDG-PET/CT was positive and helpful in finding the diagnosis. Predictive markers for a diagnostic (18)F-FDG-PET/CT were age over 50 years (p=0.019), C-reactive protein (CRP) level over 30 mg/L (p=0.002) and absence of fever (p=0.001).(18)F-FDG-PET/CT scanning is helpful in ascertaining the correct diagnosis in more than 50% of the cases presenting with FUO and IUO. Absence of intermittent fever, higher age and elevated CRP level increase the likelihood for a diagnostic (18)F-FDG-PET/CT.
EVALuna2:13447